Efeltifitas Pendidikan Islam Di Panti Asuhan Muhammadiyah Pasarbatang Berebes tahun 2010-2015 - Karim, Abdul; , Drs. Syaifuddin Zuhri, M.Ag (2016)
Muhammadiyah Orpanage (MO) of Pasarbatang Brebes is as part of the Contruction Assembly Race, Muhammadiyah should have a strategic role to educate the foster care children. Islamic education for them is the process of teaching at early stage, they will more easily understand of islamic learning until they can apply it in their life. The research focus is the effectiveness of Islamic education in Muhammadiyah orphanage (MO) Pasarbatang Brebes for foster care children. This researtch aims at knowing major problems in the research are the effectiveness in providing Islamic education to the Muhammadiyah orphanage theys Pasarbatang Brebes in 2010-2015, and what are the suppostive and barrier factors in the Islamic education process to the children. The research is a field one research. Methods of the research are interview, observation, and documentation. The technique in analyzing the data is descriptive qualitative analysis. From this research can be drawn same conclusions: (1) the effectiveness of Islamic Education conducted by Orphanage Muhammadiyah of Pasarbatang Brebes can be able to act the task or function based on trust, plan or program can be run properly, the rule should be executed well, whereas the achievement of goal or ideal conditions are in process', (2) Islamic Education Models which used by the people are providing a model, advice, conditioning, reward and punishment', (3) supporting factors are their personalities, good condition of place, having good structure of daily activities, while the barrier factors come from their own selves who have different backgrounds, and external factors influence from the outside environment, and bad relation. Key words: effectiveness, Islamic education and foster care children